Teaching English Pronunciation At The Sixth Year Of Sd Negeri Kauman Blora - Wijaya, Dharista Annike (2012)
This research is conducted to describe The component of teaching English Pronunciation at the sixth year of SD Negeri Kauman Blora and to describe the problems faced by the teacher in teaching English pronunciation, The data of the study are the information found in teaching English pronunciation. The data include participants for, student, teacher, the process of teaching and learning, syllabus, and teacher plans. In this research is descriptive qualitative, the methods of collecting are observation and documentation. The result shows that 1) The component of teaching English Pronunciation word at the sixth year of SD Negeri Kauman Blora are: syllabus, instruction materials, evaluation, technique of teaching pronunciation. 2) The problem faced by the teacher in teaching pronunciation are: Personality factor, Less capability of intonation, time management.